Design of Compact MIMO Antenna for 5G/Ultra-Wideband Communications - Pankaj Kumar Singh; Amit Sehgal; Dinesh Kumar Singh (Journal of Electronic Design Engineering, 2018)
In this contribution, a compact 13 GHz notched band Multiple-Input Multiple-Output (MIMO) antenna is accessible for Ultra-Wide Band/broadband communication in metric linear unit wave band. The antenna structure has been designed on one substrate of FR-4 of thickness 1.6 mm. Two symmetrical microstrip patch antenna elements positioned in vertical direction to realised better diversity performance. The antenna elements are made up of a rectangular patch with microstrip feed line, operatingon the frequency of 28 GHz for Ultrawide band applications. The result of designed structure has been computed numerical by FEM based solver HFSS v 13. From the simulation results, it is clear that the proposed MIMO antenna structure covers 24.048 GHz to 37.04 GHz with impedance bandwidth of 13 GHz (S11 better than -10dB) and also the isolation is found better than -20 dB in full wideband application. The gain of proposed MIMO antenna designed structure has found approximately 2.11 dB.